DETERMINASI KUALITAS LABA PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Safitri, Indhira; Ajengtiyas, Ayunita; Saebani, Akhmad (Jurnal Akunida, 2021)
This study aims to determine empirically the effect of capital structure, firm size, profit growth and liquidity as well as profitability and firm age as control variables on earnings quality in manufacturing sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. This research is a type of qualitative research that uses secondary data in the form of company annual reports. This study used a sample of 99 manufacturing companies. The technique for analyzing the data in this study uses a regression model selection test, classical assumption test, multiple linear regression, and partial hypothesis testing with STATA version 16. Based on the results of data analysis, it can be concluded that (1) capital structure, earnings growth and profitability have a negative effect on earnings quality, (2) firm size has a positive effect on earnings quality, (3) liquidity and firm age have no effect on earnings quality.